Intelligent Control and Automation International Conference on Intelligent Computing, ICIC 2006, Kunming, China, August, 2006 - Huang, De-Shuang; Irwin, George William (Lecture Notes in Control and Information Sciences, 2006)
"Intelligent Control and Automation" constitutes the results of the International Conference on Intelligent Computing, ICIC 2006, held in Kunming, China, in August 2006. The carefully reviewed contributions are included in five volumes of edited books, including one volume of Lecture Notes in Computer Science (LNCS), one volume of Lecture Notes in Artificial Intelligence (LNAI), one volume of Lecture Notes in Bioinformatics (LNBI), and two volumes of Lecture Notes in Control and Information Sciences (LNCIS). The 142 revised full papers of this volume were reviewed and selected from over 3000 submissions. The papers are organized in 4 topical sections on Blind Source Separation, Intelligent Sensor Networks, Intelligent Control and Automation as well as Data Fusion, Knowledge Discovery, and Data Mining. In addition there is a special session on Special Session on Smart and Intelligent Home Technology.